2016
DOI: 10.1007/s10404-015-1686-x
|View full text |Cite
|
Sign up to set email alerts
|

Centrifuge-based deterministic lateral displacement separation

Abstract: This work investigates the migration of spherical particles of different sizes in a centrifugedriven deterministic lateral displacement (c-DLD) device. Specifically, we use a scaled-up model to study the motion of suspended particles through a square array of cylindrical posts under the action of centrifugation. Experiments show that separation of particles by size is possible depending on the orientation of the driving acceleration with respect to the array of posts (forcing angle). We focus on the fractionat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…[69] with permission from the Royal Society of Chemistry (CC BY 2017), Ref. [70] with permission from Springer Nature, copyright 2016, Ref. [54] with permission from Springer Nature (CC BY 2016) diameter, while the elastomeric compression for reducing the gap size is more difficult to perform.…”
Section: Mechanical Stretchingmentioning
confidence: 99%
See 2 more Smart Citations
“…[69] with permission from the Royal Society of Chemistry (CC BY 2017), Ref. [70] with permission from Springer Nature, copyright 2016, Ref. [54] with permission from Springer Nature (CC BY 2016) diameter, while the elastomeric compression for reducing the gap size is more difficult to perform.…”
Section: Mechanical Stretchingmentioning
confidence: 99%
“…b Active tuning of the critical diameter using dielectrophoresis force [ 69 ]. c Centrifugal-driven DLD for modulation of forcing angles [ 70 ]. d Gravity-driven DLD for modulation of forcing angles [ 54 ].…”
Section: Factors Influencing the Dld Critical Diametermentioning
confidence: 99%
See 1 more Smart Citation
“…A well established field in microfluidics is particle enrichment and fractionation [Beech et al, 2012, Lenshof and Laurell, 2010, Sajeesh and Sen, 2014, with many promising technologies such as filtration [Chen et al, 2014, Maria et al, 1 2015, Jiang et al, 2018], deterministic lateral displacement [Huang et al, 2004, Liu et al, 2010, McGrath et al, 2014, inertial microfluidics [Godino et al, 2015, Hood et al, 2016, Ghadami et al, 2017, and centrifugation [Morijiri et al, 2013, Al-Faqheri et al, 2017. Combinations of the above mentioned methods have also been demonstrated [Marchalot et al, 2014, Jiang et al, 2016, Prabhakar et al, 2015, Kim et al, 2009. Owing to the ease of operation and scalability [Dijkshoorn et al, 2017], industrial applications range from algal harvesting [Barros et al, 2015, Olgae, 2015, where high throughputs are essential, to more conventional lab-on-a-chip applications such as diagnostics [Nam et al, 2016, Warkiani et al, 2015, Maria et al, 2017.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to size separation, DLD has been successfully applied in microfluidic systems to separate species with different shapes and deformability 6 7 8 9 10 . It was originally proposed as a flow driven, passive separation method but we have recently shown that active , force-driven DLD (f-DLD) is also effective in separating species by size 11 12 13 and shape 10 . In the majority of DLD systems the obstacle array is a periodic arrangement of cylindrical posts, but other obstacle shapes have been studied to enhance performance 14 or to separate non-spherical particles 9 .…”
mentioning
confidence: 99%